Theory of social defense and measures to combat crime in Islamic law - Ibrahim Mohamed, Hossam El Din (s.n, 2012)
The theory of social defense is one of the first theories in the modern era which relied on the precautionary measures in the fight against crime, and treatment of criminal behavior. There is no doubt that Islamic law has pioneered the use of precautionary measures to crack down on crime before it occurs, and worked to create a community of faith and the fear of God, the love of the virtues and show them, all this before the imposition of punishment.